Nano-sized plate-like alumina synthesis via solution combustion. Issue 8 (1st June 2019) - Liu, Wenqiang; Liu, Xuguang; Zhang, Pingping; Wang, Zhiyi; Li, Xia; Hu, Maocong
Abstract: Nano-sized plate-like alumina is an important inorganic material in catalytic, ceramic and electronic applications due to its unique two-dimensional structure and properties, while its facile synthesis is still under investigation. In this work, nano-sized alumina plate was synthesized by solution combustion method with glycine and polyvinyl alcohol as composite fuels for the first time. The calcination temperature during solution combustion process was optimized as confirmed by XRD, FT-IR, TG-DSC, Raman, 27 Al MAS NMR, SEM, TEM, and N2 physisorbtion. Obtained alumina displayed special nano-sized plate morphology and porous structure. It was further adopted as support for cobalt acetate and used as catalyst for selective oxidation of cyclohexane. This work develops a facile approach to synthesize two-dimensional plate-like alumina for catalytic application.